Neology in children’s literature: A typology of occasionalisms - Cécile Poix (Lexis: Journal in English Lexicology)
In literature, writers have the liberty to deviate from linguistic norms under a principle known as poetic license. Poetic license allows deviation in favour of making language inspiring. Deviation from linguistic norms often implies that writers can take liberties with word formation, thus neology in literary contexts should be addressed specifically. This article analyses the status of literary coinages in the scope of neology and describes the specific context of children’s literature. The article also offers a typology of nonce  formation processes for occasionalisms, with textual analysis, from a corpus of children’s books, using J. Tournier’s matrices of lexicogenesis [2007: 51].